Unshrinking : how to face fatphobia - Manne, Kate (Crown, 2024)
"The definitive takedown of fatphobia, drawing on personal experience as well as rigorous research to expose how size discrimination harms everyone, and how to combat it--from the acclaimed author of Down Girl and Entitled. For as long as she can remember, Kate Manne has wanted to be smaller. She can tell you what she weighed on any significant occasion: her wedding day, the day she became a professor, the day her daughter was born. She's been bullied and belittled for her size, leading to extreme dieting. As a feminist philosopher, she wanted to believe that she was exempt from the cultural gaslighting that compels so many of us to ignore our hunger. But she was not. Blending intimate stories with the trenchant analysis that has become her signature, Manne shows why fatphobia has become a vital social justice issue. Over the last several decades, implicit bias has waned in every category, from race to sexual orientation, except one: body size. Manne examines how anti-fatness operates--how it leads us to make devastating assumptions about a person's attractiveness, fortitude, and intellect, and how it intersects with other systems of oppression. Fatphobia is responsible for wage gaps, medical neglect, and poor educational outcomes; it is a straitjacket, restricting our freedom, our movement, our potential. In this urgent call to action, Manne proposes a new politics of "body reflexivity"--a radical reevaluation of who our bodies exist in the world for: ourselves and no one else. When it comes to fatphobia, the solution is not to love our bodies more. Instead, we must dismantle the forces that control and constrain us, and remake the world to accommodate people of every size"--Provided by publisher.